PENGARUH METODE JOYFUL LEARNING MENGGUNAKAN MEDIA LEGO PADA MATERI DNA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Andi Taskirah; Ninah Wahyuni Amaliah (Pendidikan Bilogi, FKIP, Universitas Muslim Maros, 2025)
Learning motivation is a fundamental determinant of students’ academic success and achievement. However, DNA structure material is often perceived as tedious due to its conceptual complexity and conventional teaching methods. This study aims to analyze the effect of a Lego media-based joyful learning approach on enhancing students' motivation in learning DNA structure. The research adopts a quantitative methodology, with participants consisting of 30 Class XII Science students from SMA Negeri 18 Makassar. Motivation data was collected using a 12-statement ARCS (Attention, Relevance, Confidence, and Satisfaction) questionnaire and analyzed through descriptive statistical techniques. The collected data included total scores and mean scores obtained by students. Response options followed a 3-point Likert scale, ranging from highly positive to highly negative (e.g., always, sometimes, never). The findings demonstrate that joyful learning using Lego media significantly improves both learning quality and student motivation. This is evidenced by the students' responses across 12 statement aspects, achieving an average score of 86.3. The interactive and engaging nature of the method actively involved students in the learning process. Thus, it is concluded that Lego-based joyful learning is highly effective in boosting student motivation in DNA structure material.